Associative versus dissociative binding of CO to 4d transition metal trimers: A density functional study - Addicoat, M.; Buntine, Mark; Yates, B.; Metha, G. (Wiley, 2008)
Density functional calculations were performed to determine equilibrium geometrical structures, transition states and relative energies for M3 clusters (M = Nb, Mo, Tc, Ru, Rh, Pd, Ag) reacting with CO, leading to proposed reaction pathways. For the Nb3, Mo3, and Tc3 clusters, the lowest energy structure correlates to dissociated CO, with the C and O atoms bound on opposite sides of the metal triangle. For all other trimers, the lowest energy structures maintain the CO moiety. In the case of Pd3 and Ag3 the dissociated geometries lie higher in energy than the sum of the separated reactants. In most cases, several multiplicities were found to be similar in energy and for Mo3CO and Pd3CO singlet-triplet minimum energy crossing points were identified. In the case of Rh3CO, minimum energy crossing points for the doublet, quartet, and sextet reaction pathways were determined and compared. The electron densities of pertinent M3CO species were investigated using Natural Bond Order calculations. It was found that the effect of the metal trimer on the energy of the pure p-type π* antibonding orbital of carbon monoxide directly correlates with the occurrence of CO dissociation.